Glandular odontogenic cyst of the mandible: A case report and literature review - Antao, Candice Jacinta; Dinkar, Ajit Dattatray; Khorate, Manisha Maruti; Carvalho, Karla (Indian Journal of Case Reports, 2018)
Glandular odontogenic cyst (GOC) is a rare developmental odontogenic cyst that has gained special attention primarily due to its aggressive potential and the microscopic features, it shares with central mucoepidermoid carcinoma of the jaws. This relatively new entity has a prevalence rate of 0.17% and lacks pathognomonic clinicoradiographic features, making the correct diagnosis a major challenge. This report describes a case of GOC presenting as a solitary osteodestructive lesion in the anterior mandible of a 54-year-old male. Cone-beam computed tomography (CBCT) images revealed a multilocular radiolucent lesion with bicortical expansion, cortical thinning, and perforation, indicating an aggressive potential. Histopathology revealed pseudoglandular epithelium with daughter cysts within the stroma, suggesting an invasive nature. The patient was diagnosed and treated in our institution. In view of the high probability of recurrence of GOC, CBCT evaluation and histopathological examination are essential. An aggressive treatment approach is recommended followed by long-term follow-up.